2013
DOI: 10.1186/1756-0500-6-283
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial profile and antimicrobial susceptibility pattern in septicemia suspected patients attending Gondar University Hospital, Northwest Ethiopia

Abstract: BackgroundBacterial blood stream infection constitutes a significant public health problem and it is an important cause of morbidity and mortality in hospitalized patients. The aim of this study was to assess the prevalence of bacterial isolates from septicemia suspected patients and their antimicrobial susceptibility pattern in Gondar University Hospital.MethodsThis laboratory based retrospective study of 390 blood culture and susceptibility tests was conducted in Bacteriology Laboratory of the University of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

54
89
14

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(157 citation statements)
references
References 16 publications
54
89
14
Order By: Relevance
“…CoNS was mainly recognized as mere contaminants till 1970's; however, several studies have now reported an increasing incidence of infection by this group of bacteria [19,20]. The isolation of CoNS is consistent with the study of Arora et al [11] and Karlowsky et al [20] where the reported isolation of the organism was 42% and 21%, respectively.…”
Section: Discussionsupporting
confidence: 80%
“…CoNS was mainly recognized as mere contaminants till 1970's; however, several studies have now reported an increasing incidence of infection by this group of bacteria [19,20]. The isolation of CoNS is consistent with the study of Arora et al [11] and Karlowsky et al [20] where the reported isolation of the organism was 42% and 21%, respectively.…”
Section: Discussionsupporting
confidence: 80%
“…Overall the range of drug resistance pattern for gram positives was from 0% -89.7% and from 0% -100% for gram negative bacteria, which is similar to the result from other part of Ethiopia, which was 0-85.7% and 0% -100% for gram negative and positive respectively. 20 This increased resistance in this study may be an indication of indiscriminate and continuous use of antibiotics as clearly seen in our study, where more patients (66.7%) were put on the wrong treatments. Thirty six (87.7%) of the S. aureus isolates were resistant to Trimethoprim-sulphamethoxazole, 34(82.9%) to ceftriazone 31(75.6%) to doxycycline, 51% to erythromycin, 39% to Gentamicin.…”
Section: Discussionmentioning
confidence: 72%
“…21,23,24 . CoNS were mainly recognized as a contaminant until the 1970's, nevertheless, several studies have reported an increasing incidence of infections due to these bacteria 25,26 . This was similar to our current study.…”
Section: Discussionmentioning
confidence: 99%
“…Irrespective of geographical locations, a worldwide SENTRY study showed that, about 70-75% of CoNS are resistant to methicillin [10]. There is a significant increase in the methicillin-resistant coagulase negative staphylococci (MR-CoNS) infections and these bacteria have recently started to gain resistance to other widely used antibiotics [11][12][13][14].The increased recognition of pathogenic potential of CoNS and emergence of drug resistance among them justify the need to identify various species of CoNS and determine their antibiotic resistance pattern. Epidemiological data about CoNS in Palestine are either scarce or insufficient [15].…”
mentioning
confidence: 99%